Off Headset: Essays on Stage Management Work, Life, and Career. - Jaen, Rafael (Routledge, 2022)
Off Headset is a collection of chapters containing essays by a richly diverse group of stage management professionals and educators covering the challenges stage managers face on the job, in their lives, and in their careers.The book starts with the intersectional history of stage managers and The actors' union. In "Part 1: Work," the contributors share a wide range of experiences, from regional theater and Broadway to operas and cruises-and even running with the circus. The essays in "Part 2: Life" explore the relevance of stage managers claiming their identity, their resilience, and practicing self-care. Finally, in "Part 3: Career," readers receive aspirational and business advice for life in the real world: leadership, networking, unemployment, managing demanding calendars, and career planning.The book ends with a moment of pause during tech-a direct response to the absence we have been enduring throughout the COVID-19 pandemic and a tribute to a world we used to take for granted. Intertwining practical advice with personal anecdotes, Off Headset: Essays on Stage Management Work, Life, and Career is the perfect accompaniment to students studying stage management in a university setting and professionals working in the field.and Career is the perfect accompaniment to students studying stage management in a university setting and professionals working in the field.and Career is the perfect accompaniment to students studying stage management in a university setting and professionals working in the field.